Indigenous farmers’ perceptions of problems in the rice field agroecosystems in the upper Baram, Malaysia - Hollaus, Alexander; Schunko, Christoph; Weisshaidinger, Rainer; Poline, Bala; Vogl, Christian R. (BMC, 2022)
Background: Rice field agroecosystems produce food for more than half of the world’s population and deliver important services supporting farmers’ livelihoods. However, traditional rice field agroecosystems are facing a variety of problems, including pests or markets that are hard to access. This research explored indigenous farmers’ perceptions of the problems, their causes and consequences, and the solutions applied to address them in the rice field agroecosystem. Furthermore, the study investigated how indigenous farmers related these problems to the surrounding landscape elements and to microzones in the fields.